(untitled) (The Pakistan Development Review, 2006)
Rarely a month passes-by in Pakistan without complains on the state of basic commodity markets, be it wheat or sugar, cotton or rice. Prices are too high for the consumers, or too low for the farmers; and often the government is asked to intervene, buying for or selling from stocks, prohibiting export or import, increasing or reducing import duties, introducing/withdrawing export taxes, or taking other measures to protect the consumer or producer. It is as if domestic prices can have a life on their own, with the government asked to guarantee “fair” prices for everbody. The resulting on-and-off policy intervention by the government is likely to have had a deleterious effect on the development of the domestic and international trade for these commodities. This is because of the uncertainty so generated, with the private traders always facing the risk of a regime change at a time when import or export contracts have already been signed. As a result too, the role of the state-owned Trading Corporation of Pakistan self-perpetuates, even if the government would like to see it minimised, as it is always being asked to intervene because of the private sector’s “failings”.